Sociolinguistic Analysis of the New Testament : Theories and Applications - Ong, Hughson T. (Biblical Interpretation Series, 2022)
This book introduces sociolinguistic criticism to New Testament studies. The individual essays cover a wide range of sociolinguistic theories (multilingualism, speech communities and individuals, language and social domains, diglossia, digraphia, codeswitching, language maintenance and shift, communication accommodation theory, social identity theory, linguistic politeness theory, discourse analysis, conversation analysis, register analysis, interactional sociolinguistics, ethnography of communication, etc.) that treat topics and issues pertaining to the language and sociolinguistic contexts of the New Testament, social memory, orality and literacy, and the oral traditions of the Gospels, and various texts and genres in the New Testament.